Exploring pre-calculus final assessment marks between gender with principal component analysis / Najihan Awang @ Ali, Nurul Husna Jamian and Muhammad Aslam Mohd Safari - Awang @ Ali, Najihan; Jamian, Nurul Husna; Mohd Safari, Muhammad Aslam (Universiti Teknologi MARA, Perak, 2021)
Pre-Calculus covers additional algebraic and trigonometric, where the students are encouraged to become proficient in those topics to prepare for an in-depth calculus learning. In Universiti Teknologi Mara (UiTM), practically every semester the issue of Pre-Calculus' high failure rate is commonly reported. One of the ways to measure the students' understanding of this subject is through the final assessment performance. Besides, gender significance is one of the most notable studies in mathematics performance. Therefore, this study aims to compare the performance of part 1 diploma students who registered Pre-Calculus in UiTM Tapah in in accordance to their gender. To analyze the results, this study performed Descriptive and Principal Component Analysis using R statistical software. It was found that the students faced problems in answering Question 2, but scored more marks for Question 5. This revealed that most of the students faced difficulties in handling sketches of parabolas and circles. It was also discovered that the female students outperformed the males in this course.